Streaming Platforms in Sports Communications: Analisys of ‘Tiempo de Juego’ on COPE Radio - González Orozco, José Vicente; Cortés Gómez, Sara (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This research examines the entry of streaming platforms into the world of sports radio, within traditional media. In this case, it analyses the incursion of YouTube as a platform for live content, which has been chosen by the main radio programmes to expand their content to other audiences. The objective is to study the growth, development and evolution of the ‘Tiempo de Juego’ channel from its beginnings on the platform, based on the treatment of its figures, content management, content structure and live hours.